Analysis of liquid–liquid droplets fission and encapsulation in single/two layer microfluidic devices fabricated by xurographic method - Lim, Chang Nong; Koh, Kai Seng; Ren, Yong; Chin, Jit Kai; Shi, Yong; Yan, Yuying (MDPI, 2017)
This paper demonstrates a low cost fabrication approach for microscale droplet fission and encapsulation. Using a modified xurography method, rapid yet reliable microfluidic devices with flexible designs (single layer and double layer) are developed to enable spatial control of droplet manipulation. In this paper, two different designs are demonstrated, i.e., droplet fission (single layer) and droplet encapsulation (double layer). In addition, the current fabrication approach reduces the overall production interval with the introduction of a custom-made polydimethylsiloxane (PDMS) aligner. Apart from that, the fabricated device is able to generate daughter droplets with the coefficient of variance (CV) below 5% and double emulsions with CV maintained within 10% without involvement of complex surface wettability modification.